2020
DOI: 10.1038/s41598-020-73984-3
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of CD38 and supplementation of NAD+ attenuate axon degeneration in a mouse facial nerve axotomy model

Abstract: Following facial nerve axotomy, nerve function is not fully restored even after reconstruction. This may be attributed to axon degeneration/neuronal death and sustained neuroinflammation. CD38 is an enzyme that catalyses the hydrolysis of nicotinamide adenine dinucleotide (NAD+) and is a candidate molecule for regulating neurodegeneration and neuroinflammation. In this study, we analyzed the effect of CD38 deletion and NAD+ supplementation on neuronal death and glial activation in the facial nucleus in the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…): 323.8 ([M + H] + ). (6). A mixture of 2,4-dichloro-6-iodoquinoline (5; 29.0 g, 89.5 mmol) in conc.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…): 323.8 ([M + H] + ). (6). A mixture of 2,4-dichloro-6-iodoquinoline (5; 29.0 g, 89.5 mmol) in conc.…”
Section: Chemistrymentioning
confidence: 99%
“…Cellular NAD + concentrations have been shown to decline during senescence, and CD38 deletion in knockout mice (KO) has proven efficacious in multiple models of neurodegeneration and has delayed aging. [4][5][6] Hence, maintaining NAD + levels and subsequent cellular homeostasis may offer a therapeutic strategy for attenuating aging and age-related neurodegenerative illnesses. An approach to maintaining NAD + levels could be to downregulate CD38 function.…”
Section: Introductionmentioning
confidence: 99%
“…The NF-kB signaling pathway is one of the main signaling pathways involved in the emergence of SASP (27), and most pro-inflammatory genes expressed in aging cells are related to NF-kB (28). The activation of tissue resident macrophages in SASP and the inflammatory environment causes the accumulation of macrophages in the liver, which expresses more CD38, showing increased signs of aging, and tending to promote inflammatory polarization (24). Covarrubias et al found that aging cells gradually accumulated in the visceral white adipose tissue and liver during aging.…”
Section: The Change Of Cd38 Expression On Macrophage Is Involved In T...mentioning
confidence: 99%
“…Supplementation with NAD + could slow down axonal degeneration and demyelination, but did not change the level of macrophage infiltration after amputation. CD38 deletion and NAD + supplementation may have an autonomic protective effect on axonal cells after facial nerve transection ( 24 ). Normal or pathological aging is characterized by an increase in the number of aging cells in the brain, mainly astrocytes, which display SASP and are characterized by the release of pro-inflammatory cytokines and chemokines.…”
Section: Effect Of Cd38 On Macrophage Function and Its Possible Mecha...mentioning
confidence: 99%
“…Mitochondrial, cytosolic, and plasma membrane localization of CD38 makes it a candidate for a sensor of NAD+ levels in the cell [ 77 ]. In the brain, CD38 is expressed in neurons, astrocytes, and microglia, and is involved in the neurotransmitter action, neurodegeneration-induced neuroinflammation, tissue regeneration, and oxytocin release [ 78 , 79 , 80 , 81 , 82 ]. Some data suggest that CD38 is involved in aging-associated decline in intracellular NAD+ levels and corresponding progression of mitochondrial dysfunction in various tissues [ 83 ].…”
Section: Mitochondrial Dysfunction and Nvu/bbb Impairment In Alzheimer’s Type Neurodegenerationmentioning
confidence: 99%